Tandem RNA binding sites induce self-association of the stress granule marker protein TIA-1 - Loughlin, Fionna E; West, Danella L; Gunzburg, Menachem J; Waris, Saboora; Crawford, Simon A; Wilce, Matthew C J; Wilce, Jacqueline A (Nucleic acids research, 2021)
Abstract TIA-1 is an RNA-binding protein that sequesters target RNA into stress granules under conditions of cellular stress. Promotion of stress granule formation by TIA-1 depends upon self-association of its prion-like domain that facilitates liquid-liquid phase separation and is thought to be enhanced via RNA binding. However, the mechanisms underlying the influence of RNA on TIA-1 self-association have not been previously demonstrated. Here we have investigated the self-associating properties of full-length TIA-1 in the presence of designed and native TIA-1 nucleic acid binding sites in vitro, monitoring phase separation, fibril formation and shape. We show that single stranded RNA and DNA induce liquid-liquid phase separation of TIA-1 in a multisite, sequence-specific manner and also efficiently promote formation of amyloid-like fibrils. Although RNA binding to a single site induces a small conformational change in TIA-1, this alone does not enhance phase separation of TIA-1. Tandem binding sites are required to enhance phase separation of TIA-1 and this is finely tuned by the protein:binding site stoichiometry rather than nucleic acid length. Native tandem TIA-1 binding sites within the 3′ UTR of p53 mRNA also efficiently enhance phase separation of TIA-1 and thus may potentially act as potent nucleation sites for stress granule assembly. Graphical Abstract Graphical Abstract Self-association of TIA-1 is induced by tandem (specific or promiscuous) RNA binding sites in a manner that is finely tuned by the protein:RNA binding site ratio rather than RNA length.